Yu Qie and the New Literary Atmosphere at St. John’s University in the 1920s - FENG Yuan (Journal of Research for Christianity in China (JRCC), 2025)
Amidst the overall “blend of old and new” literary atmosphere at St. John’s University in the 1920s, Yu Qie stood out as an early representative of the “new” and more radical faction. This was evident in his active engagement with and bold experimentation in new literary creation, as well as his thoughtful consideration of the challenges facing such endeavors. To some extent, this also reflected how the university’s literary climate gradually shifted toward openness and innovation after the 1920s. On the other hand, his new literary creations were also closely tied to St. John’s University’s established tradition of drama. Thus, he was both a representative of the university’s literary atmosphere in the 1920s and a product of that very atmosphere. All these factors directly influenced the emergence of Yu Qie as a “new bourgeois novelist” in the 1940s. His unwavering commitment to the “ideological consciousness” of fiction enabled him to capture the charm of everyday life while never losing sight of the complexities of human nature. His popularization of new literary techniques and integration of dramatic methods endowed his “New Citizen Fiction” with a blend of solemnity and humor, truly achieving his dual goal of reaching a “broad audience” while revealing “the true face of human existence.”